Nitrogen-containing bisphosphonate for vascular calcification: animal experiments, systematic review and meta-analysis - Wei Xu; Guoyuan Lu; Lifeng Gong; Weigang Tang; Wei Jiang (BMC Cardiovascular Disorders)
Abstract Background The purpose of our study was to explore the effect of nitrogen-containing bisphosphonate (N-BP) on vascular calcification (VC) through animal experiments and a meta-analysis. Methods In our animal experiments, Sprague-Dawley (SD) rats were randomly divided into a control group, a VC group, a low-dose zoledronic acid (ZOL) (20 µg/kg) group and a high-dose ZOL (100 µg/kg) group. The calcification of the aortic arch was observed by alizarin red staining. The calcium content of the aortic arch was measured. In our systematic review and meta-analysis, databases, including PubMed, Embase, the Cochrane Library, China National Knowledge Infrastructure (CNKI), and the Wanfang database, were searched from their inception to December 20, 2023. Eligible studies comparing N-BP versus no N-BP in the treatment of VC were included. Results In our animal experiment, the red-stained calcification structure in the low-dose ZOL group was slightly reduced and the red-stained calcification structure in the high-dose ZOL group was significantly reduced compared with that in the VC. The calcium content in the low-dose ZOL group was slightly lower than that in the VC group, but the difference was not significant (P = 0.08). The calcium content in the high-dose ZOL group was significantly lower than that in the VC group (P < 0.0001). Our meta-analysis of human studies revealed that N-BP did not reduce the arterial calcification score (P = 0.46). Our meta-analysis of animal studies revealed that N-BP did not significantly reduce the arterial calcification score (P = 0.09), but N-BP reduced the arterial calcification area (P < 0.00001), arterial calcium content (P = 0.009) and PO4 content (P = 0.0001). Conclusions Our animal experiment revealed that high-dose ZOL inhibited VC, but low-dose ZOL did not significantly inhibit VC. Our meta-analysis of human studies revealed that N-BP was not effective in the treatment of VC, but our meta-analysis of animal studies suggested a role of N-BP in inhibiting VC.